For better or for worse: the moderating effects of personality on the marriage life satisfaction link - Boyce, Christopher J.; Wood, Alex M.; Ferguson, Eamonn (Elsevier, 2016)
On average, marriage tends to lead to temporary increases in life satisfaction, which quickly return to pre-marital levels. This general pattern, however, does not consider the personality of individuals entering into marriage. We examine whether following marriage pre-marital personality predicts different changes to life satisfaction in a sample of initially single German adults (N = 2015), completing life satisfaction measures and indicating their marital status yearly for eight years (during which 468 married). We find that conscientious women experience greater life satisfaction following marriage than less conscientious women. Our data also indicate that introverted women and extraverted men experience longer-term life satisfaction benefits following marriage. Our results refute the claim of limited life satisfaction effects from marriage and caution against relying on average effects when examining the influence of life events on well-being.